Esclavos y tierras entre posesion y titulos : la construccion social del derecho de propiedad en Brasil (siglo XIX). (Global Perspectives on Legal History, 2021)
This book examines the social construction of legal relations between people and things in Brazil during the 19th century through the analysis of court cases discussing dominion and possession over slaves and land. The chapters address topics such as the role of social recognition in situations of possession, the process of delegitimizing acts of land usage from indigenous peoples, dependent persons and women, and the widespread illegal acquisition of slaves and land.